Performance Study of stirred tank slurry reactor and fixed‐bed reactor using bimetallic Co–Ni mesoporous silica catalyst for fischer–tropsch synthesis. Issue 1 (15th July 2017) - Sun, Yong; Yang, Gang; Sun, Guangzhi; Sun, Zhi; Zhang, Lian
Abstract : The Fischer–Tropsch synthesis (FTS) was studied using mesoporous silica‐supported bimetallic Co–Ni catalyst in a fixed‐bed reactor (FBR) and a slurry continuously stirred tank reactor (CSTR) under different temperatures (from 280°C to 300°C) with syngas ratio of 2 and a total pressure of 3.5 MPa. The activity of the catalyst was higher in FBR due to complete reduction. The CSTR was found to experience a less degree of catalyst deactivation, and its CO conversion was more sensitive in responding to the variation of temperatures because of its better temperature control. The intraparticle diffusion limitation was much improved in the CSTR system due to employment of smaller particle size of the catalyst. The selectivity of gasoline fraction (C5 –C13 ) was higher in CSTR system than that in FBR at the same baseline condition. The appreciable increases of selectivity in CO2, methane, and longer‐chain hydrocarbon were observed in FBR when the comparable CO conversion was set for comparison between FBR and CSTR. Reducing the particle size of the catalyst was more effective in increasing the selectivity of lighter (C2 –C6 ) 1‐olefin in CSTR system. The FBR produced higher selectivity of longer chain (C7 +) 1‐olefin. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 553–561, 2018